Transfer of Institutions: Actors and Constraints - The Russian Case in a Global Context - Anton Oleinik (Hamburg Institute of International Economics (HWWA), 2005)
Modernity is usually thought as a complex society with clearly differentiated spheres of everyday life. It means, in particular, that economic rules do not interfere with the norms structuring political, social, scientific and other interactions. The complex, differentiated society sharply contrasts with a ,,small“ and homogeneous ,,pre-modern“ society. The process of modernization, i.e. differentiation of the spheres of everyday life, can take various forms. In an advanced country it relies on internal forces. Modernization in this context looks like an evolutionary, ,,bottom-up“ development. In a backward country (Russia and Germany in the first half of the 20th century), modernization requires a strong governmental (from the top to the bottom) intervention. Invidious comparison with more advanced and successful countries makes the state officials in backward countries accept the way of reforms. Due to the lack of the internal forces leading to an evolutionary rise of modernity, the state officials refer to the Western experience and know-how. Consequently, a ,,catch-up“ modernization naturally transforms into ,,Westernization“, the transfer of Western institutions to backward countries. As the title suggests, the paper deals with the institutional problems of such a transfer of institutions, and with the constraints, imposed on the key actors of this process, the political elite. It will be argued, that a decisive problem of political and economic modernization in Russia is that bureaucrats face soft external and internal constraints. An absolute imperative consists in institutional congruence, or the ,,elective affinity“, between the models of power relationships on which imported and traditional institutions are based. Only a passive role in carrying out reforms is reserved for non-governmental actors, which transforms their mental models into a hard constraint of reforms and prevent them from putting limits on the rulers` discretion. Consequently, there is a high risk of the transformation of modernization policies into a mechanism of the reproduction of imposed power.
Keywords: P51; P21; O17; P37; N40; B25; D73; K42; B15; A14; A13; B52; H83; 330; state bureaucracy; economic backwardness; catch-up modernization; conservative modernization; opportunism; institutional constraints; power; Sozialer Wandel; Übergangswirtschaft; Institutioneller Wettbewerb; Wissenstransfer; Westliche Staaten; Russland